KOPERASI ERA MILLENNIAL DALAMPERSPEKTIF KETAHANAN NASIONAL - Ridhuan, Syamsu (Lembaga Penerbitan Unversitas Esa Unggul, 2019)
AbstractThis paper is the result of research conducted simultaneously with community service. The existence and message of cooperatives in the industrial revolution 4.0 is very strategic and important. Because it can answer the challenges of the corporate global economy and strengthen the resilience of national security in the economy. The research was carried out by means of a survey that took samples of all the founders of the National Integrity cooperative in Jakarta. The result of the study analyzed from the primary data of the opinions and views of the respondents indicate that the empowerment of cooperative business based on family princilples still doesnot rival and compete with the corporate economy which adheres to the principles of individualist liberal economics. It recommended that the government make regulations that are more in favor of the mangement of cooperative efforts and encourage the public to be eager to develop economic enterprises from varioussectors with massive cooperative economic movements.Â Keywords : cooperatives, resilience, nationalÂ AbstrakMakalah ini merupakan hasil penelitian yang dilakukan secara bersamaan dengan kegiatan pengabdian masyarakat. Eksistensi dan peran koperasi dalam revolusi dunia industri 4.0, menjadi sangat strategis dan penting. Sebab diasumsikan dapat menjawab tantangan ekonomi global yang bersifat koporasi dan memperkuat ketangguhan ketahanan nasional di bidang ekonomi. Penelitian dilakukan dengan cara survey yang mengambil sampel seluruh pendiri Koperasi Pembauran Kebangsaan di Jakarta. Hasil penelitian yang dianaisis dari data primer pendapat dan pandangan responden menunjukkan bahwa pemberdayaan usaha-usaha koperasi yang brazaskan kekeluargaan masih belum mampu menyaingi dan berkompetisi dengan perekonomian korpororasi yang memegang teguh prinsip ekonomi liberalis-individualis. Disarankan agar pemerintah membuatregulasi yang lebih banyak berpihak kepada pengelolaan usaha-usaha koperasi dan mendorong masyarakat agar bersemangat menumbuh-kembangkan usaha-usaha ekonomi dari berbagai sektor dengan gerakan eonomi koperasi yang massif.Â Kata kunci:koperasi, ketahanan, nasional